ANALISIS KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SD NEGERI MINTORAHAYU 02 KABUPATEN PATI - Azzati, Alya citra; Mei Fita Untari; Wawan priyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on an empirical and literature review that showed that at SDN Mintorahayu 02 in Pati Regency, which found several grade I students had low reading skills. These students had difficulty recognizing letters, stringing syllables, spelling and reading sentences fluently. In addition, there has been no literacy research related to students' reading ability at this school, even though reading ability is very important for students' academic success. The purpose of this study is to describe students' beginning reading skills and analyze the inhibiting factors that affect students' beginning reading skills in grade 1 at SDN Mintorahayu 02 in Pati district. This study used a qualitative approach with observation, interview, and documentation methods involving teachers and grade 1 students. The results showed that out of 9 students, 4 students (44%) were able to read fluently and correctly, while 5 students (56%) were not able to read well. Students with low reading skills show difficulty in recognizing and distinguishing letters, reading syllables, and spelling words and sentences. This is due to 2 influencing factors, namely internal factors and external factors. Internal factors include lack of confidence, low enthusiasm and motivation to learn, and lack of reading habits. While external factors such as a less supportive school environment such as less than optimal library management and parental support in learning. Based on the results of this study, suggestions that can be conveyed are that teachers emphasize the use of varied and interesting teaching methods by teachers, as well as intensive guidance for students who have difficulty reading. Parents are expected to provide support and motivation by reading with students at home and schools are advised to optimally manage the library.